LEARNING EFFICIENCY OF ELEMENTARY SCHOOL STUDENTS THROUGH E-LEARNING IN THE DISRUPTION ERA - Muh Jauhar Navis; Honest Ummi Kaltsum (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe the implementation of learning efficiency of elementary school (SD) students through E-learning, and to know the advantages and disadvantages of its implementation. The method of this research was descriptive qualitative with literature study design. The data were collected through literature study in the form of academic manuscripts and relevant previous research including more than 20 scientific articles. Then, the data were analyzed thorugh content analysis techniques. The results revealed that 1. The implementation of learning efficiency for elementary school students through e-learning was practical and effective with the support of the ease of technology and internet in teaching and learning activities; 2. The advantages of implementing learning efficiency for elementary school students through e-learning in the disruption era were students and teachers could easily share information, and it saved costs, energy, and time in getting maximum results; besides, the students could learn actively and independently. On the other hand, the disadvantages of implementing the learning efficiency of elementary school students through e-learning in the disruption era was the lack of interaction between teachers and students, teachers tended to ignore social and academic aspects, and not all places were available on the internet. Based on these results, this research implied that teachers and students should be able to use e-learning wisely and the government should address the gap in internet access in Indonesia, especially in remote areas.